FREE EXTRACELLULAR DNA IN NORMAL STATE AND UNDER PATHOLOGICAL CONDITIONS - V. А. Kozlov (Медицинская иммунология, 2014)
Abstract. The paper represents a synopsis of current publications concerning existence of free extracellular DNA. Such DNAs are not associated with cells of the organism, being revealed in nearly all body fluids. Recent data show that the cell-free DNA is determined in normal, healthy organism as well. Increased level of free DNA plasma and serum are detectable in many diseases, including autoimmune disorders, malignant neoplasias, myocardial infarction, etc. In many cases, free DNA may be suggested as predictive markers for various distinct diseases, as well as worsening of their clinical course. Physiological role of free DNA is not yet clear, like as its importance in development of certain diseases. It was shown that free DNA may exert stimulatory or suppressive effects upon functions of immunocompetent cells. Free extracellular DNA may also perform an inducing role for autoimmune conditions. In addition, one may assume that free DNA may be a carrier of genetic information in the body between tumor and normal cells in the body, like as between normal cells in various organs and tissues.